Critical Damage Analysis of WC-Co Tip of Conical Pick due to Coal Excavation in Mines - Saurabh Dewangan; Somnath Chattopadhyaya; Sergej Hloch (Advances in Materials Science and Engineering)
WC-Co based tools are widely used in the field of coal and rock excavation because of their unique combination of strength, hardness, and resistance to abrasive wear. Conical pick is one of the coal cutting tools. The tip of the pick is made of WC-Co material. As coal and rock are heterogeneous elements, they pose various constraints during excavation. As a result the tools wear out during the process. Other parameters like cutting techniques, tool orientation, and environmental conditions also affect the tool significantly. The wearing phenomenon greatly reduces the service life of the tools and thereby cuts down the production rate. To prevent such wearing process, it is important to investigate the different wear mechanisms in WC-Co. Simultaneously, there has to be an ongoing endeavour for the development of better quality WC-Co. This paper focuses on different wear mechanisms in a conical pick which has been used in a continuous miner machine for coal cutting. The worn out surface has been observed by using FE-SEM (field emission scanning electron microscopy) and EDS (energy dispersive X-ray spectroscopy). The mechanisms, namely, coal/rock intermixing, cracking and crushing of WC grains, and adhesion of rock particles, have been predominantly investigated in this study. A little indication of corrosive decay in the WC grain has also been reported. The EDS has detected material concentration in a selected area or point of the worn-out surface. The spectrograph confirms the presence of coal/rock materials. Elements such as W, C, Ca, K, O, and Co have been mainly found in different concentrations at different positions.